2020
DOI: 10.3390/math8060965
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Measures for Plithogenic Sets and Applications in Multi-Attribute Decision Making

Abstract: Plithogenic set is an extension of the crisp set, fuzzy set, intuitionistic fuzzy set, and neutrosophic sets, whose elements are characterized by one or more attributes, and each attribute can assume many values. Each attribute has a corresponding degree of appurtenance of the element to the set with respect to the given criteria. In order to obtain a better accuracy and for a more exact exclusion (partial order), a contradiction or dissimilarity degree is defined between each attribute value and the dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In the future, we will apply the expert weight combination weighting scheme proposed in this paper to situations in real life. We will also formulate this kind of entropy measure and similarity measures for an interval-valued IF set [56], Fermat fuzzy set, spherical fuzzy set, t-spherical fuzzy set, picture fuzzy set, single valued neutrosophic set [55,57], Plithogenic set [58] and linear fuzzy set.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we will apply the expert weight combination weighting scheme proposed in this paper to situations in real life. We will also formulate this kind of entropy measure and similarity measures for an interval-valued IF set [56], Fermat fuzzy set, spherical fuzzy set, t-spherical fuzzy set, picture fuzzy set, single valued neutrosophic set [55,57], Plithogenic set [58] and linear fuzzy set.…”
Section: Discussionmentioning
confidence: 99%
“…Sujatha et al (2020) and utilized the plithogenic cognitive map to analyze the data related to the corona virus. Quek et al (2020) presented an entropy measure, while Bala (2020) discussed the information fusion measures for the plithogenic set. Ahmad et al (2021) presented an optimization model for the supply chain problems by utilizing the neutrosophic set features.…”
Section: A Plithogenic Application To Decision-making Problemsmentioning
confidence: 99%
“…It is also revealed that the Plithogenic Whole Hyper-Soft Matrix (PWHS Matrix) is a special case of the Plithogenic Subjective Hyper-Super-Soft Matrix (PSHSS Matrix). Additional literature on Hyper-Soft Set and Plithogency can be found in [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%